New products, quality changes and welfare measures computed from estimated demand systems - Nevo, Aviv (NBER working paper series, 2001)
This paper examines the construction of a price index based on an estimated demand system. In principle the method examined can produce a price index that accounts for introduction of new products and quality changes in existing products. However, I isolate two key assumptions that have to be made in order to interpret the demand estimates into welfare measures. Using estimates of a brand-level demand system for ready-to-eat cereal I demonstrate the empirical importance of the assumptions. For the data I use, depending on the interpretation of the demand estimates, a price index can range between a 35% percent increase over the five years examined to a 2.4% decrease.